The Mediation Role of Audit Quality: Impact Internal Audit Strategy, Auditor Ethics, and Accounting Culture on Financial Report Quality - Sari, Gema Ika; Suhaili, Ahmad; Lesfandra, Lesfandra (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The quality of financial reporting in regional banks is becoming increasingly complex in meeting future demands, leading to a dependence on audit quality as the basis for making informed decisions. However, the problem lies in the fact that regional banks need to place internal audits in a strategic role to support the quality of financial reporting. The research aims to determine the mediating role of audit quality on the impact of internal audit strategy, auditor ethics, and accounting culture on the quality of financial reporting. The research method used a quantitative approach with a study population of 60 internal auditors. The sampling technique used was saturated sampling. The data analysis techniques used were SEM-PLS. The study results show a significant and positive influence of internal audit strategy, auditor ethics, and accounting culture on the quality of financial reporting, both directly and mediated by audit quality. Based on research lies in the practical impact of improving the quality of financial reporting by strengthening accounting culture through professionalism, optimism, flexibility, and transparency.